IDDF2019-ABS-0111 Colorectal cancers detected following surgery at anastomoses or other colorectal locations during colonoscopy surveillance – a systematic review and meta-analysis. (June 2019) - Fuccio, Lorenzo; Rex, Douglas; Ponchon, Thierry; Frazzoni, Leonardo; Dinis-Ribeiro, Mario; Bhandari, Pradeep; Dekker, Evelien; Pellise, Maria; Correale, Loredana; Hooft, Jeanin van; Jover, Rodrigo; Libanio, Diogo; et al.
Abstract : Background: Outcomes of endoscopic surveillance following surgery for colorectal cancer (CRC) vary with the incidence and timing of CRC detection, at anastomosis or elsewhere in the colorectum. We performed systematic review and meta-analysis to evaluate the incidence of CRCs identified during surveillance colonoscopies of patients with previous CRC surgery. Methods: We searched PubMed, EMBASE, SCOPUS, and the Cochrane Central Register through January 1, 2018, to identify studies investigating rates of CRCs at anastomoses or other colorectal locations after curative surgery for primary CRC. We collected data from randomized controlled, prospective, and retrospective cohort studies. Data were analyzed by multivariate meta-analytic models. Results: From 2, 373 citations, we selected 27 studies with 15, 803 index CRCs (89% stage I-III CRCs). Overall, 296 CRCs at non-anastomotic locations were reported over time periods of more than 16 years (cumulative incidence, 2.2% of CRCs; 95% CI, 1.8%-2.9%). The risk of non-anastomotic CRC is shown in figure A (figure 1A ) and significantly decreased after 36 months or more from resection, compared with that before this time point (odds ratio for non-anastomotic CRCs at 36–48 months vs 6–12 months after surgery, 0.61; 95% CI, 0.37–0.98; P=.031); 53.7% of all non-anastomotic CRCs were detected within 36 months from surgery. One hundred fifty-eight anastomotic CRCs were detected over more than 16-years follow-up (cumulative incidence of 2.7%; 95% CI, 1.9%-3.9%). The risk of anastomotic CRCs is shown in figure B (figure 1B ), and was significantly lower after 24 months or more from resection than before (odds ratio for CRCs at anastomoses at 25–36 months after surgery vs. 6–12 months, 0.56; 95% CI, 0.32–0.98; P=.036); 90.8% of anastomotic CRCs were detected within 36 months from surgery. Conclusions: After surgery for CRC, the highest risk of anastomotic and non-anastomotic CRCs is highest during 36 months after surgery - risk decreases thereafter. Patients who have undergone CRC resection should be evaluated by colonoscopy more closely during this time period. Longer intervals may be considered thereafter.